Ectopic lymphoid structures in the aged lacrimal glands (2023)
ABSTRACT: Aging is a complex biological process in which many organs are pathologically affected. We previously reported that aged C57BL/6J had increased lacrimal gland (LG) lymphoid infiltrates that suggest ectopic lymphoid structures. However, these ectopic lymphoid structures have not been fully investigated. Using C57BL/6J mice of different ages, we analyzed the transcriptome of aged murine LGs and characterized the B and T cell populations. Age-related changes in the LG include increased differentially expressed genes associated with B and T cell activation, germinal center formation, and infiltration by marginal zone-like B cells. We also identified an age-related increase in B1+ cells and CD19+B220+ cells. B220+CD19+ cells were GL7+ (germinal center-like) and marginal zone-like and progressively increased with age. There was an upregulation of transcripts related to T follicular helper cells, and the number of these cells also increased as mice aged. Compared to a mouse model of Sjögren syndrome, aged LGs have similar transcriptome responses but also unique ones. And lastly, the ectopic lymphoid structures in aged LGs are not exclusive to a specific mouse background as aged diverse outbred mice also have immune infiltration. Altogether, this study identifies a profound change in the immune landscape of aged LGs where B cells become predominant. Further studies are necessary to investigate the specific function of these B cells during the aged LGs.